Extracorporeal membrane oxygenation use in the first 24 hours following pediatric heart transplantation: Incidence, risk factors, and outcomes. (11th April 2019) - Godown, Justin; Bearl, David W.; Thurm, Cary; Hall, Matt; Feingold, Brian; Soslow, Jonathan H.; Mettler, Bret A.; Smith, Andrew H.; Profita, Elizabeth L.; Singh, Tajinder P.; Dodd, Debra A.
Abstract: Primary graft dysfunction following HTx is associated with significant morbidity and mortality. This study aimed to assess the incidence of, risk factors for, and outcomes of children requiring ECMO within 24 hours of HTx. This study utilized a linked PHIS/SRTR database of pediatric HTx recipients (2002‐2016). Post‐HTx ECMO was identified using inpatient billing data. Logistic regression assessed risk factors for post‐HTx ECMO. Kaplan‐Meier analyses assessed in‐hospital mortality and post‐discharge survival. A total of 2820 patients were included with 224 (7.9%) requiring ECMO. Independent risk factors for post‐HTx ECMO include age <1 year (aOR: 2.2, 95% CI: 1.3‐3.7, P = 0.006) or 1‐5 years (aOR: 2.1, 95% CI: 1.3‐3.4, P = 0.002), and ECMO support at HTx (aOR: 27.4, 95% CI: 15.2‐49.6, P < 0.001). Survival to discharge decreased with increasing duration of post‐HTx ECMO support; 89% for 1‐3 days, 79.1% for 4‐6 days, 63.2% for 7‐9 days, and 18.8% for ≥10 days. There was no difference in long‐term survival for patients requiring post‐HTx ECMO who survived to hospital discharge ( P = 0.434). There are identifiable risk factors associated with the need for ECMO in the post‐HTx period. Length of time on ECMO post‐HTx is strongly associated with the risk of in‐hospital mortality. Patients who require ECMO early post‐HTx and survive to discharge have comparable outcomes to patients who did not require ECMO.